Chromosome 7p linkage and association study for diabetes related traits and type 2 diabetes in an African-American population enriched for nephropathy - Gallagher Carla J; Keene Keith L; Langefeld Carl D; Leak Tennille S; Lu Lingyi; Mychaleckyj Josyf C; Rich Stephen S; Freedman Barry I; Bowden Donald W; Sale Michèle M (BMC, 2010)
Abstract Background Previously we performed a linkage scan of 638 African American affected sibling pairs (ASP) with type 2 diabetes (T2D) enriched for end-stage renal disease (ESRD). Ordered subset linkage analysis (OSA) revealed a linkage peak on chromosome 7p in the subset of families with earlier age of T2D diagnosis. Methods We fine mapped this region by genotyping 11 additional polymorphic markers in the same ASP and investigated a total of 68 single nucleotide polymorphisms (SNPs) in functional candidate genes (GCK1, IL6, IGFBP1 and IGFBP3) for association with age of T2D diagnosis, age of ESRD diagnosis, duration of T2D to onset of ESRD, body mass index (BMI) in African American cases and T2D-ESRD in an African American case-control cohort. OSA of fine mapping markers supported linkage at 28 cM on 7p (near D7S3051) in early-onset T2D families (max. LOD = 3.61, P = 0.002). SNPs in candidate genes and 70 ancestry-informative markers (AIMs) were evaluated in 577 African American T2D-ESRD cases and 596 African American controls. Results The most significant association was observed between ESRD age of diagnosis and SNP rs730497, located in intron 1 of the GCK1 gene (recessive T2D age-adjusted P = 0.0006). Nominal associations were observed with GCK1 SNPs and T2D age of diagnosis (BMI-adjusted P = 0.014 to 0.032). Also, one IGFBP1 and four IGFBP3 SNPs showed nominal genotypic association with T2D-ESRD (P = 0.002-0.049). After correcting for multiple tests, only rs730497 remanined significant. Conclusion Variant rs730947 in the GCK1 gene appears to play a role in early ESRD onset in African Americans.